Optimasi Waktu dan Suhu Pemeraman untuk Meningkatkan Kualitas Analog Keju secara Mikrobiologis, Fisiko-Kimia, dan Sensori - Fajrul Arief; Lia Agustin; Agnesia Bunga Nurhayati (Perum BULOG, 2026)
Background: The increasing popularity of vegan lifestyles and plant-based diets has driven the food industry to seek cheese alternatives. Consequently, this research aimed to develop a product comparable to conventional cheese.Objectives: Notably, the novelty of this study lies in combining Geotrichum candidum with varying ripening times and temperatures to improve the microbiological, physicochemical, and sensory qualities of vegan cheese. Methods: To achieve this, a completely randomized design was used to test two factors: time and temperature. Additionally, data were analyzed using ANOVA and DMRT. Results and Discussion: The results indicated that ripening time significantly influenced viability, pH, proteolysis, lipolysis, water content, moisture-free-fat-basis (MFFB), flavor, and texture (p<0.01), as well as fat-in-dry-matter (FDM) and ash content (p<0.05). Furthermore, ripening temperature was directly proportional to viability, proteolysis, lipolysis, FDM, flavor, texture, fat, protein, and ash content, but inversely proportional to pH, water content, and MFFB (p<0.01). Importantly, interaction effects between time and temperature were seen in viability, proteolysis, lipolysis, flavor, and texture (p<0.05). Conclusion: Based on these findings, the recommended ripening method is D4T3, at 15 °C for 90 days. This approach, therefore, resulted in cheese analogues with optimal microbiological (viability, proteolysis, and lipolysis of 5.54 log CFU/mL, 3.55 mM Gly/L, and 24.21 µmol oleate/hour, respectively), physicochemical (MFFB 59%, water content 55%, protein 21%, FDM 17%, ash 13%, fat 10%), and sensory (flavor and texture preferred by panelists) qualities under the experimental conditions.